Analysis of Experimental Estimates Power Coronа Losses on Overhead Intersystem Power Transmission Lines - Kuchanskyy, V. V.; Zaitsev, I. O.; Kovalenko, O. M. (Visnyk of Vinnytsia Politechnical Institute, 2024)
Interest in the study of coronation is related to energy losses during coronation of power transmission lines. Thus, energy losses in case of crowning of wires of ultra-high voltage power transmission lines in bad weather are very significant. The method of measuring power loss per corona is described. The main task of which can be divided into two parts: determining the full charges of each of the three phases of the transmission line and directly measuring the power loss. The basis of the first task is the use of antennas and the subsequent solution of the system of equations. The validity of the described method was experimentally substantiated in laboratory conditions. For this purpose, a laboratory model of a three-phase line with a length of l = 14.5 m with a height of suspension of wires above the plane H = 2 m and a distance between phases D = 1.3 m was mounted, while steel wires with a diameter of 1 mm were used. Under each phase of the line at a height of h = 0.27 m, antennas are installed - copper wires of the same length as on the line. The antennas were grounded using capacitors, from which the voltages were applied to the oscilloscope and visualized. All three voltages, proportional to the charges of the corresponding antennas, were applied in turn to the oscilloscope and photofixation of one frame was carried out. A special synchronizing device made it possible to obtain three time-matched curves on each oscillogram. Charge curves and volt-coulomb characteristics are constructed under conditions of changing phase voltages, up to values exceeding the initial corona voltage by more than 3 times. Thus, we obtained data on power losses per corona on the wires of the experimental laboratory line in a wide range of voltages. A detailed experimental study of the antenna method for measuring corona power losses was performed in the laboratory on the experimental line, where the conditions are close to the conditions of actual intersystem power transmission lines. These studies confirmed the conclusions obtained on the basis of laboratory experiments. An experimental study fully confirmed the possibility of measuring corona power losses on intersystem power transmission lines using antennas.